EDUKASI DAN PENDAMPINGAN KESADARAN HUKUM HAK KEKAYAAN INTELEKTUAL (HKI) BAGI PELAKU UMKM DESA - Rommy Hardyansah; Fayola Issalillah; Rafadi Khan Khayru; Rahayu Mardikaningsih; Mirza Elmy Safira; Didit Darmawan; Rio Saputra (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2026)
This strategic initiative which involves branding, informative banners and visual signage for micro-business products in Pasinan Village, Pasuruan Regency is designed to enhance the appeal of these products whilst strengthening the identity of the businesses. This empowerment initiative applies the Asset-Based Community Development (ABCD) framework, which focuses on optimising local resources and carefully analysing market opportunities, particularly in the ‘es jaran’ product line, which is noted for having relatively few competitors. Programme implementation is centred on the Monas Market area, Lekok Sub-district, Pasuruan, as a means of accelerating growth and market penetration within the micro-enterprise sector. Findings from the programme’s implementation indicate that the use of visual promotional materials has proven effective in increasing the visibility of the product, enhancing competitiveness, and expanding the scope of marketing. Through the formulation of coherent marketing tactics and the strengthening of the distribution supply chain, business operators in Pasinan now have a far greater chance of succeeding in the competition within a much larger market.